Non-audit services and the corporate governance of audit clients / Khairul Anuar Kamarudin, Wan Adibah Wan Ismail and Jessieca Cherryl Yatan. - Kamarudin, Khairul Anuar; Wan Ismail, Wan Adibah; Yatan, Jessieca Cherryl (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam:, 2019)
This paper investigates the relationship between corporate governance qualities and the purchase of non-audit services among Malaysian Listed Companies. The sample consists of 709 companies listed on Bursa Malaysia during the year 2014. The study posits that CEO duality, board independence, audit comitte independence, big 4 auditors, the audit committee size, and the frequency of audit committee meetings are associated with the amount of non-audit services. This is basically based on the argument that weaker governance allows the company to jeopardise the independence of external auditor, hence higher level of non-audit services. Company size, profitability, leverage, growth and industry are also included in the study as the control variables. Using the ordinary least square regression model and relevant diagnostic tests, findings shows that only board independence, audit committee independence, audit committee size and big 4 auditors are associated with the level of non-audit services. The results of this study contribute to the present literature on the determinants of non-audit services, especially in emerging market. The result would also be informative to regulators worldwide when considering to apply new policies related to non-audit services.